2020
DOI: 10.36783/18069657rbcs20200097
|View full text |Cite
|
Sign up to set email alerts
|

Total fungi and yeast distribution in soils over native and modified vegetation in central Brazil

Abstract: Fungi are ubiquitous components of soil microbial communities, generally comprise the largest proportion of soil biomass. They can occur as filamentous forms or unicellular yeasts, in both, as free-living or symbionts. Next generation sequencing has allowed greater depth of the access to soil fungal diversity complementing culture-dependent results. In Brazil, the state of Minas Gerais is recognized for its mining activity, which modifies the vegetation cover and consequently the soil microbial communities. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The authors suggested that the elevated species richness in a revegetated area points to a possible ecological role of yeasts in environmental recovery. Moreira et al (2020) reported on soil fungal diversity in a postmining area, comparing natural and modified environments by metabarcoding of the ITS2 region. The authors compared the soil fungal communities of biomes with different vegetation types and levels of human intervention, ranging from none to high environmental impact (Atlantic Rain Forest, iron outcrops, Eucalyptus , and grass).…”
Section: Yeast Diversity In Tropical Forests and Related Forest Biome...mentioning
confidence: 99%
“…The authors suggested that the elevated species richness in a revegetated area points to a possible ecological role of yeasts in environmental recovery. Moreira et al (2020) reported on soil fungal diversity in a postmining area, comparing natural and modified environments by metabarcoding of the ITS2 region. The authors compared the soil fungal communities of biomes with different vegetation types and levels of human intervention, ranging from none to high environmental impact (Atlantic Rain Forest, iron outcrops, Eucalyptus , and grass).…”
Section: Yeast Diversity In Tropical Forests and Related Forest Biome...mentioning
confidence: 99%